La personalidad y el estilo de aprendizaje: una relación mutua en el rendimiento académico en la clase de inglés - Morales Rojas, Yuri (2016)
The aim of this study is to identify the personality types and learning styles of a group of students in their first year of the Computer Science Major to determine the effect they have on the oral and written skills in their English as a foreign language class. The total study population consists of twenty three learners who were taking the course English Integrated Skills for Other Majors, level II, during the second term 2015 at Universidad Nacional in Costa Rica. Three surveys were adapted and used to gather the data: the learning styles of Kolb, the Eysenck personality type and a third one, designed using Kolb’s description of the learning styles, to know how the learners perceive and process information in class together with observations on the students’ reactions to the activities provided by the teacher. The results indicate that there is no a direct relationship between the students’ personality and the oral and written performance contradicting what other studies said, but there is a relationship between the personality and the learning styles of the individuals and between the learning styles identified, and the oral and written production of the pupils since the learner’s styles indicate the possible reason of the difficulties that the students displayed.